2021
DOI: 10.1007/s10103-021-03344-8
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation enhances facial nerve regeneration via activation of PI3K/Akt signaling pathway–mediated antioxidant response

Abstract: Facial nerve dysfunction is a common clinical condition that leads to disfigurement and emotional distress in the affected individuals. This study aimed to evaluate whether photobiomodulation can enhance regeneration of crushed facial nerves and attempt to investigate the possible underlying mechanism of neuroprotective function and therapeutic target. Various parameters of photobiomodulation were assigned to the facial nerves and Schwann cells (SCs) separately during crushed injury in rats. Axonal regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In another study performing axonotmesis, 980 nm PBM at three points along the nerve, three times a week for 5 weeks, had a beneficial effect on facial nerve regeneration, including the better functional capacity of the vibrissae and improvement in morphological nerve changes. Furthermore, there was a decrease and excessive suppression of apoptosis in Schwann cells induced by oxidative stress via activation of the PI3K/Akt signaling pathway [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study performing axonotmesis, 980 nm PBM at three points along the nerve, three times a week for 5 weeks, had a beneficial effect on facial nerve regeneration, including the better functional capacity of the vibrissae and improvement in morphological nerve changes. Furthermore, there was a decrease and excessive suppression of apoptosis in Schwann cells induced by oxidative stress via activation of the PI3K/Akt signaling pathway [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential of laser light to impact the peripheral nervous system has been explored in both the neuromuscular and somatosensory systems. This investigation dates to 1978 when it was discovered that laser radiation directed at exposed nerve tissue had a direct and beneficial effect as a preventive measure and a therapeutic intervention [23]. Currently, the preferred treatment for peripheral nerve injuries is advanced microsurgical repair or autologous nerve grafting.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on rats showed that treatment with PBM significantly helped repair nerve fibers. This effect was associated with an increase in the activity of certain enzymes in utilizing the ATP—phosphoinositide 3-kinases/protein kinase B (PI3K/Akt) cellular signaling pathway, crucial for many cell functions, including energy management and cell growth [ 12 ].…”
Section: Pathophysiological Aspects Of Tbi and Related Pbm Researchmentioning
confidence: 99%
“…Axonal Injury PBM may aid axonal recovery through improved ATP generation and modulation of secondary mediators. It activates the PI3K/Akt signaling pathway [11,12].…”
Section: Pathophysiological Aspects Description Of the Pbm Researchmentioning
confidence: 99%